(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
When it comes to crop breeding, the rate at which yields improve is not fast enough to keep up with the growing world population. In plant breeding, the extremely extended harvest period limits the creation of superior crop types. Because of the several processes of cross-breeding, selection, and testing, it can take up to two decades for a new cultivar to be established. New plant varieties can help relieve food shortages and food instability. Traditional agricultural techniques have resulted in a decrease in crop genetic diversity. To increase agronomic qualities like as yield quality and resilience to biotic and abiotic stressors in agricultural plants by genetic selection and mutagenesis breeding, somaclonal variants, physical mapping, and functional genomics methods have been applied. Clustered palindromic repeats and programmable nucleases are used in gene editing (CRISPR). Plant breeders and the rest of the world are taking use of cutting-edge techniques like speed breeding, genome editing, and high-throughput phenotyping to increase crop breeding efficiency.